Nanodefect substructures in crystal phosphors; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Lisitsyn V. M. Viktor Mikhailovich (2015, 2015)
Title screen